You should first recognize the shape of the curve - it's an exponential function, so its equation takes the form
for some constants a, b, and c.
The curve lies above the x-axis, so a must be positive.
The curve is defined everywhere (there are no discontinuities), so b must be positive.
As you move left to right, the function is increasing, so c must also be positive. But to make things simpler, let's assume c = 1.
When x = 0, the curve passes through the point (0, 1). In our equation, we have
![y(0) = a\cdot b^0 = a](https://img.qammunity.org/2022/formulas/mathematics/college/uk1uaq83pmixdoni1kf1wxq0ohu00s9gza.png)
so it follows that a = 1.
When x = 1, the curve approximately passes through the point (1, 4); so
![y(1) = b^1 = 4](https://img.qammunity.org/2022/formulas/mathematics/college/fd1fxsmypcn3adkeeowg8wmt0a799nyp6z.png)
so b = 4.
Then the equation of the curve might be
.